La3+ and Dy3+ hexaaza macrocycles revisited: Enhanced stabilization of G-quadruplex DNA - spectroscopic and in silico studies - Ewert, Ernest; Marcinkowski, Dawid; Pospieszna-Markiewicz, Izabela; Palumbo, Rosanna; Hnatejko, Zbigniew; Kubicki, Maciej; Gorczyński, Adam; Wieczorek-Szweda, Ewelina; Patroniak, Violetta; Roviello, Giovanni N.; Fik-Jaskółka, Marta (International journal of biological macromolecules, 2025)
This study explores the synthesis and characterization of two 18-membered hexaaza macrocyclic complexes formed from pyridine-2,6-dicarbaldehyde and trans-1,2-diaminocyclohexane, coordinated with La3+ and Dy3+ ions. We investigate their stabilizing effects on G-quadruplex (G4) structures associated with telomeric DNA sequences (Tel26, Tel22) and the c-myc oncogene promoter (Pu22) with regards to the nature of central ions. Using UV-melting and circular dichroism (CD) spectroscopy, we demonstrate that the [LaL]3+ complex exhibits superior stabilization of these G4 structures compared to [DyL]3+. 1H NMR titrations confirm interactions of both macrocyclic complexes with target molecules. Further in silico docking studies confirmed it and revealed possible significant binding interactions between [LaL]3+ and hTERT G4 DNA occurring through the coordination of the metal ion with the O6 atom of G15 residue in the central cavity of the G4 structure. Moreover, the TDS and CD spectra of the randomly coiled Tel26 sequence incubated with [LaL]3+ indicate its folding into a G4-like structure. Overall, these findings position [LaL]3+ as a promising candidate for further investigation in cancer treatment strategies. •La(III)/Dy(III) hexaaza macrocycles stabilize G4 DNA, synthesized via one-step template reaction.•[LaL]3+ shows stronger G4 affinity/stabilization than [DyL]3+, due to differences in central ion properties.•Docking shows lanthanide cation crucially binds G4 central channel via key interactions.